Association between the Life's Essential 8 Health Behaviors and Prognosis in Patients with Advanced Cardiovascular-Kidney-Metabolic Syndrome - Muhammad Ansar Maqsood, Muhammad Sikandar Saleem, Ibtisam Ilahi, Muhammad Azhar Khan, Abdur Rauf Hammad, Syeda Nosheen Zehra, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Cardiovascular-Kidney-Metabolic (CKM) syndrome is a recently recognized multisystem condition that encompasses the coexistence of cardiovascular disease, chronic kidney disease, and metabolic dysfunction. Patients with advanced CKM syndrome experience poor prognosis, yet the impact of lifestyle and behavioral health factors on outcomes remains underexplored. The American Heart Association’s Life’s Essential 8 (LE8) offers a standardized framework to assess cardiovascular health behaviors and biological risk factors. Objectives: To evaluate the association between LE8 health behaviors and prognosis in patients with advanced CKM syndrome, and to identify the individual components most predictive of adverse outcomes. Methods: This prospective observational study was conducted at Evercare Hospital, Lahore, and Liaquat National Hospital, Karachi, between June 2022 and June 2023. A total of 120 patients with advanced CKM syndrome were enrolled. LE8 scores were calculated for each participant, and patients were categorized into low (0–49), intermediate (50–79), and high (80–100) cardiovascular health groups. The primary outcome was all-cause mortality at 12 months, while secondary outcomes included major adverse cardiovascular events (MACE), renal function decline (≥30% reduction in eGFR), and CKM-related hospitalizations. Results: Of the 120 patients, 40 were categorized as low CVH, 48 as intermediate CVH, and 32 as high CVH. During the 12-month follow-up, mortality rates were significantly higher in the low CVH group (32.5%) compared to intermediate (14.6%) and high CVH groups (6.3%, p=0.01). The incidence of MACE (45.0% vs. 27.1% vs. 15.6%, p=0.02) and renal decline (40.0% vs. 27.1% vs. 15.6%, p=0.04) also followed this trend. Cox regression analysis identified poor blood pressure control, nicotine exposure, and poor sleep health as independent predictors of mortality. Conclusion: Higher LE8 scores were strongly associated with improved survival, reduced cardiovascular events, slower renal decline, and fewer hospitalizations in patients with advanced CKM syndrome. Lifestyle modification and adherence to LE8 health behaviors, particularly blood pressure control, smoking cessation, and healthy sleep, should be prioritized alongside pharmacological management. LE8 scoring may serve as a practical clinical tool for risk stratification and patient counseling in CKM care. Keywords: Life’s Essential 8, cardiovascular-kidney-metabolic syndrome, prognosis, cardiovascular health, renal outcomes, lifestyle modification.